Student Learning Model Enhancement: How Does the Project-Based Learning Model Affect Students' Critical Thinking Skills? - Meganing Ati; Ayu Adriyaningsih; Taridi Taridi; Candra Kusuma; Widi Astuti; Sutiyono Sutiyono; Komang Sutawan (International Journal of Science and Applied Science: Conference Series, 2024)
This study explores the influence of project-based Learning Models on critical thinking. Project-based Learning makes a significant contribution to developing students' critical thinking skills. Students involved in PJBL tend to be more active in the learning process, can ask in-depth questions, and have the ability to analyze and reflect on information critically. The research used a quantitative approach with a survey method. Respondents in this study were elementary school students. The research population was 47 students, obtained through the proportional random sampling technique—respondents of elementary school students in the 2024 academic year. The study results showed a significant favorable influence between Project Learning and students' Critical Thinking with a t count of 72.0 and a significance value (p) of 0.000 <0.05. From the simple regression analysis calculation results, the R Square value was 28.0. Project Learning affects critical Thinking by 72.0%, and other factors influence the remaining 28.0%.